Culture and the performance of teams in complex systems - A Hodgson; Ella-Mae Hubbard; Carys Siemieniuch (2011)
The practice of systems engineering is becoming more formalized. However, this formalization is aimed primarily at the technical and process components of complex systems. National cultural variations in the human components of such systems (typically functioning as groups or teams) are not typically included in the formal specifications and, as a result, the technical end-products do not fully compensate for these variations. This paper provides an introduction to culture, its measurement and its effects on team performance. The paper then describes a methodology and software tool for the assessment of the cultural traits of team members and the estimation of the effects of team culture on task or mission performance. The paper concludes that, despite some disparities in the results of research studies, sufficiently strong relationships between culture and team performance have been established to justify the representation of user culture in systems engineering toolsets.